Perlindungan Masyarakat Adat Terhadap Penggunaan Sumber Daya Genetik Dan Pengetahuan Tradisional Dalam Invensi Perspektif Traktat Internasional Wipo 2024 - sari, Mieke yustia; Cita Yustisia Serfiyani; Yatini; Masda Agatha Sari (PROGRESIF: Jurnal Hukum, 2025)
Treaty on intellectual property, genetic resources and traditional knowledge 2024 approved an international agreement that is a breakthrough for the development of intellectual property. This paper aims to analyze the form of protection for indigenous peoples in the utilization of genetic resources used in patented research according to the international treaty WIPO and the urgency of the treaty for the development of patents in Indonesia. The approach used in this study is the statute approach and the analytical approach. The international treaty that began negotiations in 2001 is a strategic step for the development of intellectual property, especially indigenous peoples as holders of rights to genetic resources and traditional knowledge. Its use is often used in research to produce new inventions that are protected by patents. In such conditions, the applicant must disclose indigenous peoples as providers of traditional knowledge. The treaty is very important for the development of patents in Indonesia as well as strategic protection for traditional knowledge and genetic resources owned by Indonesia. Patented inventions containing genetic resources and traditional knowledge clearly disclose their material sources, thereby increasing the transparency of patent protection.